2019
DOI: 10.37358/rc.18.12.6761
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Alginate Beads for Intestinal Ketoprofen Delivery

Abstract: Herein, studies on ketoprofen delivery systems based on silica-alginate beads developed for the drug intestinal release for reducing its side effects were reported. The influence of surface properties, pore size and geometry of mesoporous silica carriers on the ketoprofen release kinetics was studied by using pristine and 3-aminopropyl functionalized MCM 41 (Mobile Composition of Matter) and MCF (mesocellular foam silica) materials. The ketoprofen loaded mesoporous silica coated with alginate is a pH-triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Herein, we report studies on the synthesis of mesostructured silicaetitania SBA-15etype composites with up to 30 mol % titania by a solegel technique combined with a hydrothermal treatment, which were further explored as carriers for oxytetracycline. Previously, we reported that oxytetracycline-loaded into MCM-41 silica and aluminosilicate mesopores [27] or silicaeceria MCM-41etype composites [28] presented a burst release effect followed by a sustained delivery from MCM-41etype support and exhibited a good antibacterial activity against five clinical isolates of Staphylococcus aureus strains. [27] By modification of the SBA-15 matrix through the introduction of titania we expect to enhance the interactions between drug molecules and mesoporous silicaetitania composites leading to a slower antibiotic release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report studies on the synthesis of mesostructured silicaetitania SBA-15etype composites with up to 30 mol % titania by a solegel technique combined with a hydrothermal treatment, which were further explored as carriers for oxytetracycline. Previously, we reported that oxytetracycline-loaded into MCM-41 silica and aluminosilicate mesopores [27] or silicaeceria MCM-41etype composites [28] presented a burst release effect followed by a sustained delivery from MCM-41etype support and exhibited a good antibacterial activity against five clinical isolates of Staphylococcus aureus strains. [27] By modification of the SBA-15 matrix through the introduction of titania we expect to enhance the interactions between drug molecules and mesoporous silicaetitania composites leading to a slower antibiotic release kinetics.…”
Section: Introductionmentioning
confidence: 99%